Dampak Return on Asset dan Return on Equity terhadap Harga Saham PT Bank Mandiri Tbk Kurun Waktu 2011 Hingga 2020 - Supriatna, Agus (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study aims to investigate how two key financial ratios, Return on Assets (ROA) and Return on Equity (ROE), influence the stock price of PT. Bank Mandiri Tbk. The data spans from 2011 to 2020, covering a period of 10 years. A quantitative research method was employed to collect and analyze the data. To ensure the robustness of the findings, several classical assumption tests were conducted. These tests assess the reliability of the regression analysis model and ensure that the underlying assumptions of normality, multicollinearity, heteroscedasticity, and autocorrelation are met. By using SPSS version 26, regression analysis was performed to determine the relationship between ROA, ROE, and the stock price. The results indicate that both ROA and ROE significantly influence the stock price when considered together. This conclusion is based on the F-statistic value of 23.117, which exceeds the critical F-value of 4.74 at a 95% confidence level (? = 5%). This means that the independent variables, ROA and ROE, have a statistically significant collective impact on the stock price of PT. Bank Mandiri Tbk during the period under study. In summary, the study provides evidence that the financial performance indicators (ROA and ROE) are strong predictors of stock price movements, offering valuable insights for investors and stakeholders in evaluating the company's market value.